1992
DOI: 10.1161/01.hyp.20.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Resting and maximal forearm skin blood flows are reduced in hypertension.

Abstract: To find whether the vasodilator capacity of nonacral skin is reduced in hypertension, we measured forearm blood flow by venous occlusion plethysmography in 10 seated norcnotensive (mean±SD mean arterial pressure, 94±5 mm Hg) and 10 hypertensive (112±9 mm Hg) men at rest for 39 minutes while the forearm was heated with water at 42°C, a maneuver known to selectively and maximally vasodilate skin. Blood pressure, measured every 5 minutes, did not change with heating. We found that in the nonnotensive group restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
2
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 28 publications
7
69
2
3
Order By: Relevance
“…This was indicative of a reduced functional response of the cutaneous microcirculation after ischaemia in the hypertensive patients. In contrary to Carberry et al, 7 our results did not show a reduction in maximum laser Doppler flow during cutaneous heating in the hypertensives compared with the controls (160 vs 175, P ¼ NS). This discordance can be accounted for by methodological differences.…”
Section: Impairment Of Porh But Not Hyperhemy At 44 1c In the Hypertecontrasting
confidence: 99%
See 1 more Smart Citation
“…This was indicative of a reduced functional response of the cutaneous microcirculation after ischaemia in the hypertensive patients. In contrary to Carberry et al, 7 our results did not show a reduction in maximum laser Doppler flow during cutaneous heating in the hypertensives compared with the controls (160 vs 175, P ¼ NS). This discordance can be accounted for by methodological differences.…”
Section: Impairment Of Porh But Not Hyperhemy At 44 1c In the Hypertecontrasting
confidence: 99%
“…This technique has evidenced deteriorations during ageing, diabetes and hypertension. [6][7][8][9][10][11][12] However, this technique will only be of value if the cutaneous microcirculation can be used as a mirror of the vital territories (cerebral, renal and coronary), which are more difficult to access. Indeed, Holowatz et al 13 recently urged for study of the relations between the pathological modifications of these different microcirculations.…”
Section: Introductionmentioning
confidence: 99%
“…Kenney and co-workers (5,8) found that skin temperature was similar between hypertensive and normotensive individuals and that the increases in forearm blood flow were reduced in hypertensive individuals during periods of rising internal temperature induced by dynamic exercise. Carberry and co-workers (21) observed that hypertension reduces the maximal cutaneous vasodilation induced by local warming of the forearm skin. Nevertheless, the cited studies did not separate forearm muscle blood flow from cutaneous blood flow and Kellogg Jr. and co-workers (7) found that cutaneous vascular conductance was probably greater in hypertensive than in normotensive subjects during passive heat stress.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5] Tem sido ainda utilizada como um modelo de investigação em vários estados patológi-cos como a diabetes do tipo II, [6] a doença vascular periférica [1] e a hipertensão [7] . No contexto clínico as variáveis microcirculatórias são utilizadas como ferramentas de prognóstico para avaliar a isquémia grave dos membros [8] , a evolução da ferida cutânea [9] e, até para determinar o nível de amputação.…”
Section: Introductionunclassified
“…[3][4][5] It has been used as a research model in various diseases such as type II diabetes [6] peripheral vascular disease [1] and hypertension. [7] Clinically, microcirculatory variables are also used as prognostic tools to assess severe limb ischemia, [8] wound outcome [9] and also to eventually determine the amputation level. [10] Laser Doppler Flowmetry (LDF), Transcutaneous Gasimetry and Evaporimetry are extensively used technologies that enable sensitive, continuous, non-invasive and real-time assessment of circulation related variables.…”
Section: Introductionmentioning
confidence: 99%